75.7k views
3 votes
Someoneeeeee pleaseeeeee help meeee​

Someoneeeeee pleaseeeeee help meeee​-example-1
User Androboy
by
5.2k points

1 Answer

1 vote

Answer: x=60

Explanation:

x+22+x+6+x−28=180

Step 1: Simplify both sides of the equation.

x+22+x+6+x−28=180

x+22+x+6+x+−28=180

(x+x+x)+(22+6+−28)=180(Combine Like Terms) 22+6=28 and then 28-28=0

3x=180

3x=180

Step 2: Divide both sides by 3.

3x/3 = 180/3

x=60

hope this was helpful.

User Jalem
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.